Between two unions : Europeanisation and Scottish Devolution. - Dardanelli, Paolo (Devolution series., 2006)
This book is the first in-depth comparative study of Scottish devolution and the first to analyse the impact of the European dimension. With focus on the periods leading up to the referendums in 1979 and 1997, it investigates positions and strategies of political parties and interest groups and how these influenced constitutional preferences at mass level and ultimately the referendum results. Based on rigorous analysis of an extensive body of quantitative and qualitative sources, it builds a ground-breaking argument that challenges the widespread thesis that support for devolution was a conse.